2016
DOI: 10.1186/s12870-016-0771-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant hormone-mediated regulation of stress responses

Abstract: BackgroundBeing sessile organisms, plants are often exposed to a wide array of abiotic and biotic stresses. Abiotic stress conditions include drought, heat, cold and salinity, whereas biotic stress arises mainly from bacteria, fungi, viruses, nematodes and insects. To adapt to such adverse situations, plants have evolved well-developed mechanisms that help to perceive the stress signal and enable optimal growth response. Phytohormones play critical roles in helping the plants to adapt to adverse environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
1,020
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,586 publications
(1,045 citation statements)
references
References 98 publications
16
1,020
0
9
Order By: Relevance
“…ABA plays a major role in inducing and maintaining seed dormancy (Kermode 2005) and there is also vast evidence of its involvement in plant responses to environmental stresses, especially caused by abiotic factors (Verma et al 2016). There are several reports proving the connection between ABA signaling, polyamines metabolism and plant defense system (Toumi et al 2010;Marco et al 2011;Saha et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…ABA plays a major role in inducing and maintaining seed dormancy (Kermode 2005) and there is also vast evidence of its involvement in plant responses to environmental stresses, especially caused by abiotic factors (Verma et al 2016). There are several reports proving the connection between ABA signaling, polyamines metabolism and plant defense system (Toumi et al 2010;Marco et al 2011;Saha et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, SA mediates plant resistance towards biotrophic or semibiotrophic pathogens, and is involved in the systemic acquired resistance (SAR) in which a pathogenic attack on one part of the plant induces resistance in other parts; JAs and ET mediate resistance to necrotropic plant pathogens (Broekaert et al 2006; Pieterse et al 2012). Auxins, CKs, BRs, ABA and GA are mainly involved in regulating various aspects of plant growth and development, including root and shoot growth, flowering, leaf senescence, fruit ripening, seeds dormancy and germination, etc, but they may also participate in disease resistance through SA, JAs or ET signaling regulation (Jiang et al 2013; Verma et al 2016; Nolan et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found that rather YUC9 than YUC8 has a possible role in plant response to water deficit by conferring tolerance to drought. Among the known plant hormones, abscisic acid (ABA), salicylic acid (SA), jasmonic acid (JA) and ethylene (ET) are known to play important roles in mediating responses to multiple biotic and abiotic stresse (Forcat et al 2008;Verma et al 2016). Here, we demonstrated the implication of YUC8 and YUC9 in the response to spider mite attack and drought stress responses (See Sections 4.2.1 and 4.2.3).…”
Section: Resultsmentioning
confidence: 94%
“…In this context, the perception of environmental stimuli alters the concentration of several signaling molecules, including plant hormones, intracellular Ca 2+ levels, and secondary compounds such as, e.g., inositol phosphate, sugars or reactive oxygen species (Pozo et al 2015;Verma et al 2016). Among these, the phytohormones are considered the most important plant substances for regulating physiological and molecular responses.…”
Section: General Mechanism Of Interaction Between Auxin and Jasmonatesmentioning
confidence: 99%